Feedback frequency and appraisal reactions: a meta-analytic test of moderators. Issue 17 (24th September 2020) - Pichler, Shaun; Beenen, Gerard; Wood, Stephen
Abstract: Performance appraisals provide employees with feedback that helps them improve subsequent performance, with acceptance of feedback as a key precondition to improve performance. In this study, we use the due process model of performance feedback to better understand predictors of favorable employee reactions to performance appraisal. The due process model views knowledge of performance standards and frequent feedback as aspects of adequate notice in performance appraisal, and as key predictors of favorable appraisal reactions. Empirical findings to date, however, have been inconsistent on this issue. Feedback frequency has not been consistently related to appraisal reactions in primary studies, suggesting the potential for moderator effects. We therefore meta-analyzed the relationships between knowledge of performance standards and feedback frequency with appraisal reactions through the due process lens with performance rating favorability and knowledge of performance standards as moderators. Our findings suggest prior inconsistent results could be partly explained by the moderating effects of performance rating favorability and knowledge of performance standards on the relationship between feedback frequency and appraisal reactions. We discuss the implications of our results for theory, research and practice.